Assessment of the 2017 AHA/ACC/HRS Guideline Recommendations for Implantable Cardioverter-Defibrillator Implantation in Cardiac Sarcoidosis. (September 2019) - Kazmirczak, Felipe; Chen, Ko-Hsuan Amy; Adabag, Selcuk; von Wald, Lisa; Roukoz, Henri; Benditt, David G.; Okasha, Osama; Farzaneh-Far, Afshin; Markowitz, Jeremy; Nijjar, Prabhjot S.; Velangi, Pratik S.; Bhargava, Maneesh; et al.
Abstract : Background: Implantable cardioverter-defibrillators are used to prevent sudden cardiac death in patients with cardiac sarcoidosis. The most recent recommendations for implantable cardioverter-defibrillator implantation in these patients are in the 2017 American Heart Association/American College of Cardiology/Heart Rhythm Society Guideline for Management of Patients With Ventricular Arrhythmias and the Prevention of Sudden Cardiac Death. These recommendations, based on observational studies or expert opinion, have not been assessed. We aimed to assess them. Methods: We performed a large retrospective cohort study of patients with biopsy-proven sarcoidosis and known or suspected cardiac sarcoidosis that underwent cardiovascular magnetic resonance imaging. Patients were followed for a composite end point of significant ventricular arrhythmia or sudden cardiac death. The discriminatory performance of the Guideline recommendations was tested using time-dependent receiver operating characteristic analyses. The optimal cutoff for the extent of late gadolinium enhancement predictive of the composite end point was determined using the Youden index. Results: In 290 patients, the class I and IIa recommendations identified all patients who experienced the composite end point during a median follow-up of 3.0 years. Patients meeting class I recommendations had a significantly higher incidence of the composite end point than those meeting class IIa recommendations. Left ventricular ejection fraction (LVEF) >35% with >5.7% late gadolinium enhancement on cardiovascular magnetic resonance imaging was as sensitive as and significantly more specific than LVEF >35% with any late gadolinium enhancement. Patients meeting 2 class IIa recommendations, LVEF >35% with the need for a permanent pacemaker and LVEF >35% with late gadolinium enhancement >5.7%, had high annualized event rates. Excluding 2 class IIa recommendations, LVEF >35% with syncope and LVEF >35% with inducible ventricular arrhythmia, resulted in improved discrimination for the composite end point. Conclusions: We assessed the Guideline recommendations for implantable cardioverter-defibrillator implantation in patients with known or suspected cardiac sarcoidosis and identified topics for future research.